Global Responses Analysis of Submerged Floating Tunnel Considering Hydroelasticity Effects - Xiangji Ye; Xiangbo Zhou; Ming Wang; Dongsheng Qiao; Xin Zhao; Li Wang (Journal of Marine Science and Engineering)
To investigate the applicability and differences in wave loads and the dynamic response calculation principles for SFT on an entire-length scale, two numerical models of entire-length SFT with identical dimensions and parameters were established. These models are employed by a 3D diffraction method based on rigid-body assumptions, the potential flow theory and the Dummy-Connection-Mass (DCM) method based on the lumped mass method and Morison equation while considering hydroelasticity effects. The applicability of the potential flow theory and Morison equation for wave load calculation of SFT is presented along with the differences in their dynamic response calculation, which aim to explore the impact on SFT dynamic responses considering hydroelasticity by comparing the numerical calculation results. Furthermore, a comparison between free-end boundary and fixed-end boundary models, established using the DCM method, is conducted to examine the reasonableness of the commonly adopted free-end boundary condition.